Biological value of safflower protein - Murrillo, A.; F. Vega, Dolores; Vidal, Concepción; Varela, G. (Ars Pharmaceutica (Internet), 1968)
A study is made of the nutritive value of the protein of whole safflower seed fluor (Carthamus tinctorius, sifted with the object of reducting its fibre content to 24.2%. We employed the method of Thomas-Mitchell for the which enabled used to determinate the coeficient of digestibility and also the biological value f the protein. At the same time, we are determined the protein-genetic aminoacid content of this proten, using an automatic amino acid analyser, and with these results we have calculated the essential amino acid index.